Improvement of emulsifying properties of Brea gum by controlled thermal treatment - Castel, María Virginia (2018)
Brea gum (BG), which is an exudate from Cercidium praecox tree, was purified and subjected to thermal treatment at 110 °C during different times: 24, 48, 72 and 96 h. Treatment effect was evaluated by analyzing the molecular mass distribution of proteins and polysaccharides, by color and spectrophotometric analyses and by an emulsifying test. BG thermal treated presented changes in the molecular mass of its protein fractions and in its color parameters as a result of non-enzymatic browning reactions. The new molecular species generated were identified by spectrophotometry as Maillard reaction products of the different reaction phases. The modifications in BG structure produced an increase in its surface activity and improved its emulsifying/stabilizing capacity, obtaining corn oil emulsions stable for several months. Finally, the results showed that 24 h of treatment at 110 °C was enough to improve the emulsifying properties of BG.